APPLICATION OF THE DISCOVERY LEARNING MODEL MATLAB-ASSISTED TO IMPROVE THE MATHEMATICAL REPRESENTATION ABILITY OF GRADE X - Situmorang, Nengsi Syah Putri; Panjaitan, Simon M.; Pangaribuan, Lena R.; Situmorang, Adi Suarman; Hutauruk, Agusmanto J. B. (Dharmas Education Journal (DE_Journal), 2021)
This study aims to determine whether there is an improvement in students' mathematical representation ability through the implementation of the Discovery Learning model assisted by MATLAB in Grade X at SMA Swasta Parulian 1 Medan. This research is a Classroom Action Research (CAR) using the Kemmis & McTaggart model, which was conducted in two cycles. Each cycle consists of several stages: planning, action, observation, and reflection. The subjects of this study were 32 students from Class X-2 at SMA Swasta Parulian 1 Medan. Data collection techniques involved teacher activity observation sheets, student activity observation sheets, and mathematical representation ability tests. The results showed that the implementation of the Discovery Learning model assisted by MATLAB in trigonometry material could enhance students' mathematical representation ability. The percentage of students achieving classical learning mastery at the end of Cycle I was 15.62%, which then increased to 71.875% at the end of Cycle II. The improvement in students' mathematical representation ability from the beginning of Cycle I to Cycle II was categorized as medium, with an average N-Gain of 0.474. The results of teacher activity observations reached the "very good" criteria at the end of Cycle II, with an average score of 94, while student activity observations also achieved the "very good" criteria at the end of Cycle II, with an average score of 94.44.